Invisible gold in Asia: Creating wealth through intellectual property - LLEWELYN, David (Institutional Knowledge at Singapore Management University, 2010)
World competition in the 21st century will revolve around competition for intellectual property rights (IPRs). But what are these rights that you can t see the Invisible gold of today's knowledge economy. What can you do with them and how can Asian businesses foster the innovation and creativity they protect? From the patents protecting creative technology's MP3 player and Tata's Nano car to Tsingtao and Singha branded beer, IPRs protect this Invisible gold. David Llewelyn challenges Asian businesses to build up their reserves of Invisible gold and governments to build a culture that encourages and rewards innovation and creativity. Using Asian examples throughout, David Llewelyn explains what the rights are, answers the questions and sheds much-needed light on this crucial but little-understood part of doing business in the 21st century.